Pattern of Policy Network Structure in building synergy in Bandung City Society - Rizky Ilhami; Ade Rahmat; Willya Achmad (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The pattern of the policy network structure is the flow in the preparation of policy formulations. The policy network structure refers to the pattern of relations between the actors involved. The structure forms a government network between the government, stakeholders, community (society), media, academics. The purpose of this study is to determine the role of DLHK Bandung as the leading sector in determining the involvement of parties in the implementation of policies that have been set in the RTRW of Bandung City in 2011 – 2031. This writing spurs on the basis of Policy Network theory, one of the dimensions of which is structure, and research methods. by using a qualitative phenomenological approach. This study draws the conclusion that DLHK Bandung City approaches the Pentahelix system in the preparation of the annual KLHS, the involvement includes academics, business actors, NGOs and internal analysis.